Penentuan Desa Pusat Pertumbuhan Kawasan Agropolitan di Kecamatan Silo, Kabupaten Jember - Erna Fatmawati (Fakultas Teknik, 2025)
the agricultural and plantation sectors, so it can support the development of agropolitan areas. However, the management of commodity production and distribution in this area is still constrained, especially in terms of management that has not been optimized. This study aims to determine the village growth center and leading commodities using the LQ analysis method, DLQ, scalogram analysis and content analysis. The results showed that the leading commodities in Silo Sub-district include food crops (peanuts), horticulture (papaya, mangosteen, banana, guava, durian, salak, lempuyang, and key), and plantations (tobacco, coffee, coconut). Scalogram analysis resulted in three regional hierarchies, with Sempolan Village as the central growth village. Furthermore, Karangharjo, Silo, Sumberjati, and Sidomulyo villages have potential as raw material processing areas, and Mulyorejo, Pace, Harjomulyo, and Garahan villages as raw material producing areas. According to the content analysis, strategies for developing agropolitan areas include improving basic infrastructure, downstream government programs, providing training to farmers, access to capital, and strengthening institutions.
Reuploud Repository hasyim Juni 2026 Validasi file repositori 2 Juni 2026_Dea_Firli
Keywords: agropolitan area; leading commodities; regional hierarchy